Design and Build a Human Resources Management System for Bank BRI KCP 16 Ilir Palembang Based on a Dynamic Web Using PHP Native and MySQL - M. Dadi Haswinardi; Apriansyah; Dedi Haryanto (Universitas Islam Kuantan Singingi, 2025)
In Indonesia, various agencies and companies are increasingly realizing the importance of digitalization in human resource (HR) management processes. Financial institutions, such as banks, which have complex organizational structures and a large number of employees, require reliable and integrated information systems to support personnel administration effectively. Bank Rakyat Indonesia (BRI), as one of the largest and oldest banks in Indonesia, has an extensive operational network reaching the sub-district level, including the BRI Sub-Branch Office (KCP) 16 Ilir in Palembang City. This unit plays a crucial role in delivering financial services while also managing internal HR administration. However, HR management at KCP 16 Ilir is still conducted conventionally using physical documents and simple applications such as Microsoft Excel, leading to inefficiencies in data retrieval, attendance recapitulation, reporting, and performance monitoring. This study aims to address these challenges by developing a dynamic web-based human resource information system. The proposed system enables centralized employee data management, online attendance recording, digital leave submission, and performance evaluation reporting. Developed using PHP Native, MySQL, and Bootstrap, the system is designed to be cost-effective, responsive, and user-friendly, thereby improving efficiency, accuracy, and transparency in HR management at the branch level.